A multicopper oxidase-related protein is essential for insect viability, longevity and ovary development - Peng, Zeyu; Green, Peter G.; Arakane, Yasuyuki; Kanost, Michael R.; Gorman, Maureen J. (My University, 2014)
Typical multicopper oxidases (MCOs) have ten conserved histidines and one conserved cysteine that coordinate four copper atoms. These copper ions are required for oxidase activity. During our studies of insect MCOs, we discovered a gene that we named multicopper oxidase-related protein (MCORP). MCORPs share sequence similarity with MCOs, but lack many of the copper-coordinating residues. We identified MCORP orthologs in many insect species, but not in other invertebrates or vertebrates. We predicted that MCORPs would lack oxidase activity due to the absence of copper-coordinating residues. To test this prediction, we purified recombinant Tribolium castaneum (red flour beetle) MCORP and analyzed its enzymatic activity using a variety of substrates. As expected, no oxidase activity was detected. To study MCORP function in vivo, we analyzed expression profiles of TcMCORP and Anopheles gambiae (African malaria mosquito) MCORP, and assessed RNAi-mediated knockdown phenotypes. We found that both MCORPs are constitutively expressed at a low level in all of the tissues we analyzed. Injection of TcMCORP dsRNA into larvae resulted in 100% mortality prior to adult eclosion, with death occurring mainly during the pharate pupal stage or late pharate adult stage. Injection of TcMCORP dsRNA into pharate pupae resulted in the death of approximately 20% of the treated insects during the pupal to adult transition and a greatly shortened life span for the remaining insects. In addition, knockdown of TcMCORP in females prevented oocyte maturation and, thus, greatly decreased the number of eggs laid. These results indicate that TcMCORP is an essential gene and that its function is required for reproduction. An understanding of the role MCORP plays in insect physiology may help to develop new strategies for controlling insect pests.
Citation: Peng Z, Green PG, Arakane Y, Kanost MR, Gorman MJ (2014) A Multicopper Oxidase-Related Protein Is Essential for Insect Viability, Longevity and Ovary Development. PLOS ONE 9(10): e111344. https://doi.org/10.1371/journal.pone.0111344
Keywords: Multicopper oxidases; Tribolium castaneum; Anopheles gambiae